Effect of spacing and Rhizobium inoculum on the yield and quality of faba bean (Vicia faba L.) (Journal of the Bangladesh Agricultural University, 2024)
An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh to evaluate the effect of spacing and Rhizobium inoculum level on the yield and quality of faba bean. The experiment comprised of four spacings viz., 30 cm × 30 cm, 30 cm × 25 cm, 30 cm × 20 cm and 30 cm × 15 cm, and four levels of Rhizobium inoculum viz., 0, 40, 80 and 120 g kg-1 seed. The experiment was laid out in a randomized complete block design with three replications. It was observed that the highest seed yield (1.23 t ha-1) was recorded at spacing 30 cm × 20 cm which was as good as the yield (1.14 t ha-1) at 30 cm × 15 cm spacing. The highest crude fat (3.16%) and ash (4.79%) were recorded at spacing 30 cm × 20 cm while the highest crude protein (33.62%) and fibre (15.49%) were recorded at 30 cm × 25 cm and 30 cm × 30 cm spacing, respectively. In case of Rhizobium inoculum, the highest seed yield (1.04 t ha-1) and stover yield (1.75 t ha-1) were obtained in Rhizobium inoculum 80 g kg-1 seed. The highest crude protein (33.54%) and crude fat (2.82%) were recorded at Rhizobium inoculum 120 g kg-1 seed while the highest ash (4.88%) and fibre (15.28%) was recorded at Rhizobium inoculum 80 g kg-1 and Rhizobium inoculum 40 g kg-1 seed, respectively. In case of interaction, the highest seed yield (1.46 t ha-1) and stover yield (2.53 t ha-1) were obtained at 30 cm × 20 cm spacing with Rhizobium inoculum 80 g kg-1 seed. The highest amount of protein (35.73%) and ash (5.63%) were found at 30 cm × 25 cm spacing with Rhizobium inoculum 80 g kg-1 seed while the highest crude fat (4.48%) and fibre (18.04%) were recorded at 30 cm × 20 cm spacing with Rhizobium inoculum 120 g kg-1 seed and spacing 30 cm × 30 cm with control treatment of Rhizobium, respectively. Based on these results it can be concluded that spacing 30 cm × 20 cm coupled with Rhizobium inoculum 80 g kg-1 seed appears as the promising combination in respect of seed yield of faba bean.J Bangladesh Agril Univ 18(2): 245–251, 2020https://doi.org/10.5455/JBAU.91870